Qualitative Study of Breastfeeding Practice Experiences of Teenager Mothers with Unwanted Pregnancy - Wulan Wijaya; Sri Nabawiyati Nurul Makiyah; Warsiti Warsiti (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2021)
Unwanted pregnancy in many adolescents raises physical, psychological and social problems. One of the problems of unwanted pregnancy in adolescents is reluctance to breastfeed. The purpose of this study was to obtain an in-depth overview of breastfeeding practice experiences in teenage mothers with unwanted pregnancies. This research is a qualitative research with a phenomenological approach in adolescent mothers in the working area of the Gunungkidul District Health Center. Research participants were selected by purposive sampling with convenience sampling. Data collection was carried out through in-depth interviews, FGDs and observations of field notes on eight participants of teenage mothers based on interview guidelines and conducted data analysis. The results of this study the majority of teenage mothers have experience of good breastfeeding practice. Almost all teenage mothers understand exclusive breastfeeding. There are several factors that influence teenage mothers when breastfeeding, such as the experience of facing difficulties early breastfeeding. Breastfeeding decision making in adolescents is strongly influenced by parents. Experience when dealing with physical problems, such as the initial illness of breastfeeding, a little milk comes out, nipples blisters and breast swelling. Family support and health workers make teenage mothers maintain breastfeeding practices. Another factor is the information of parents, the environment, peers, health workers and the experience of people around based on the observations they make. Conclusion breastfeeding practices in adolescent mothers with unwanted pregnancies gained experience facing difficulties early breastfeeding, decision-making experiences that are strongly influenced by family members, experiences when dealing with physical problems breastfeeding.